2015
DOI: 10.1136/annrheumdis-2015-208216
|View full text |Cite
|
Sign up to set email alerts
|

Signs of immune activation and local inflammation are present in the bronchial tissue of patients with untreated early rheumatoid arthritis

Abstract: Signs of immune cell accumulation and activation are present both in the bronchial tissue and in BAL of untreated patients with early RA without concomitant lung disease, strengthening the role of the lung compartment as an important player in ACPA-positive RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 29 publications
4
59
1
1
Order By: Relevance
“…92,93 The synovial tissue of patients who are at risk of arthritis has also been examined in two relatively small studies Little evidence of synovitis was found in the first and subtle T-cell infiltration was noted in the second. 94 Data on alternative tissues such as lung and lymph node that may be important in the very early stages of arthritis as sites of first antigen presentation. 94,95 It is suggested that a 'window of opportunity' may exist during which RA can be most successfully treated.…”
Section: Early Arthritis and Early Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…92,93 The synovial tissue of patients who are at risk of arthritis has also been examined in two relatively small studies Little evidence of synovitis was found in the first and subtle T-cell infiltration was noted in the second. 94 Data on alternative tissues such as lung and lymph node that may be important in the very early stages of arthritis as sites of first antigen presentation. 94,95 It is suggested that a 'window of opportunity' may exist during which RA can be most successfully treated.…”
Section: Early Arthritis and Early Diagnosismentioning
confidence: 99%
“…94 Data on alternative tissues such as lung and lymph node that may be important in the very early stages of arthritis as sites of first antigen presentation. 94,95 It is suggested that a 'window of opportunity' may exist during which RA can be most successfully treated. In initial studies few molecular differences had been observed in the synovium comparing early and late disease.…”
Section: Early Arthritis and Early Diagnosismentioning
confidence: 99%
“…Airway changes on CT were detected more frequently in RA patients (66%) compared to controls (42%), suggesting that local airways inflammation is already present in patients recently diagnosed with RA [70]. Another study by the same investigators examined bronchial biopsy in similar patients with untreated early RA and found significant local inflammation in the lung at the alveoli and airways [71]. Adaptive immune cells (B cells, T cells, and plasma cells) were much more likely to be present and activated in CCP-positive patients compared to the CCP-negative RA patients or controls in both bronchial biopsies as well as bronchioalveolar lavage [71].…”
Section: Alveolar and Airway Inflammation In Preclinical Ramentioning
confidence: 99%
“…Reynisdottir and colleagues analyzed fluid from bronchoalveolar lavage and found increased citrullination of proteins in CCP2-positive early untreated RA patients compared to CCP2-negative RA and healthy controls [71]. Ytterberg and colleagues performed proteomic screening of bronchial and synovial biopsies of RA patients to find proteins in common at both sites that might link the lung and joints [76].…”
Section: Citrullination Of Antigens In Respiratory Mucosamentioning
confidence: 99%
“…В других исследованиях было показано, что АЦБ обнару-живаются в мокроте здоровых людей, «серопозитивных» по АЦБ или имеющих семейный анамнез по РА [131]. Вы-явлена ассоциация между развитием бронхоэктазов, фиб-роза легких и увеличением концентрации АЦБ [132], об-разованием ростковых центров и накоплением В-клеток и плазматических клеток в ткани легких АЦБ-позитив-ных людей, у которых в последующем развилcя РА [133], и увеличением содержания цитруллинированных белков (виментин) в бронхиальной и синовиальной тканях [134]. Интересно, что на ранней стадии РА, предшествующей поражению суставов, преобладает синтез аутоантител IgA-изотипа [37,49,57,135,136].…”
Section: фак торы внешней средыunclassified